Some of the developmental features of professional interests in students of Pedagogical Institute - Kregždė, S. (Psichologija, 1966)
Staff qualities are largely determined by their professional purposefulness. It is important to know their consistent patterns in the development of their professional interests, in order to improve the teacher training. Thus, in 1960-1964 in VPI, 400 students from different departments and of different study years were examined by using the questionnaire, interviews with students and their friends and an experiment in order to determine their professional interests and their developmental features. The results showed that professional interests could divide all students into two groups: a) students who choose the teacher specialty while during the admission to the institute, and b) students, who are admitted to a corresponding specialty and agree to study it at any institution of higher education without considering features of work after graduating from the institute. Developmental differences in professional interests is also characteristic to these groups.Practical conclusions:1. It is important to improve the professional purposefulness of all the subjects that are taught and at the institute and educational links.2. It is key to employ profession orientation and profession consultation in secondary school according to the needs of economy, and begin to form active professional interests in teenage years.
Keywords: professional interests; profession orientation; professional purposefulness; pedagogics students